Assessing the role of antioxidant and pro-oxidant balance in mediating the relationship between vitamin K intake and depressive symptoms in adults - Wang, Lujie; Huang, Shuling; Feng, Zhiyi; Xiao, Jianyun; Luo, Gaoquan; Zhang, Yuan (Frontiers in Nutrition, 2024)
Background: Growing evidence suggests a link between vitamin K (VK) intake and depression, although the underlying mechanisms remain unclear. We aimed to investigate whether oxidative balance scores (OBS) mediate the association between VK intake and depression in participants from the National Health and Nutrition Examination Survey (NHANES) 2007-2018.We analyzed data from 30,408 individuals. Dietary VK intake served as the independent variable, depression symptoms as the outcome variable, and OBS as the mediator. Multivariable logistic regression and restricted cubic splines assessed the associations. Mediation analysis was conducted to evaluate the potential mediating role of OBS.Results: Higher dietary VK intake was associated with lower depression risk in the multivariate model. Compared to the lowest log2 VK quartile, those in the higher quartiles had significantly lower depression odds (Q3: OR 0.66, 95% CI 0.55-0.78; Q4: OR 0.64, 95% CI 0.52-0.78). Additionally, a 1-unit increase in log2 VK intake was associated with a 15% decrease in depression odds (OR 0.85, 95% CI 0.81-0.90). Restricted cubic splines revealed a non-linear relationship between log2 VK and depression (p for non-linearity < 0.001). Notably, OBS mediated 26.09% (p < 0.001) of the association between log2 VK and depression.Higher VK intake is associated with reduced depression risk, potentially mediated by oxidative balance. Further research is warranted to confirm causality and elucidate the underlying mechanisms.